The development of semantic feedback for teaching and learning in physical education - Iskandar Y.H.P.; Gilbert L.; Wills G.B.; Basir N. (2024)
This paper generally focus on how and where linked data could be integrated and used in the development of semantic feedback for teaching and learning in physical education. Feedback may currently be generated based upon a competence model. To achieve semantic interoperability and increase the level of reusability of feedback, competence should be represented as an explicitly defined, structured, and shared ontology. By providing shareable ways of representing a competence model, hierarchy or a cyclic directed graph, human and machine would be helped to communicate easily in comparing competence structures and exchanging semantic feedback. Competence structures and semantic feedback could be published on the web using linked data principles. Linked data allows both coaches and athletes to browse the athlete's feedback and navigate the related competence structures and training materials. 2013 IEEE.